The Program Development for Enhancing the Effective Authentic Leadership on Private School Management - Ketvisetkul, Thanapakorn; Noirid, Surachet (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research was to study and develop the program for enhancing the Effective Authentic Leadership on Private School Management. The target group were the private school administrators. The research instruments were: the Interview Form, the Questionnaire, and the Self-Assessment Form. The research findings found that: 1) the components of Effective Authentic Leadership on Private School Management including 4 components and 21 indicators: (1) the Self-Awareness including 7 indicators, (2) the Balanced Processing including 4 indicators, 3) the Relational Transparency including 6 indicators, 4) the Internalized Moral Perspective including 4 indicators, 2) the overall current situation was in “Moderate” level, the overall desirable situation was in “the Highest” level, 3) the Program for enhancing the Effective Authentic Leadership on Private School Management including the following components” the Principle, Objective, Model and Technique Development, Structural Content, Knowledge Management in Program, and Program Evaluation including 4 Learning Unit: Model 1, the Confidence and Faith, Module 2, the Self-Awareness, Module 3, the Commitment and Sincerity, Module 4, the Reasonability. The Program Evaluation was in “the Highest” level. 4) the application of Program for enhancing the Effective Authentic Leadership, found that the Private School Administrators’ Authentic Leadership before development (pretest) was in “Moderate” level. After development (posttest), was in “the Highest” level. The evaluative findings of Effective Authentic Leadership on Private School Management, before development (pretest), in overall, was in “Moderate” level. After development (posttest), in overall, was in “the Highest” level.